Prevalence of disability among adults using Rapid Assessment of Disability tool in a rural district of South India. Issue 4 (October 2016) - Ramachandra, Srikrishna Sulgodu; Allagh, Komal Preet; Kumar, Hemanth; Grills, Nathan; Marella, Manjula; Pant, Hira; Mahesh, D.; Soji, Fairlene; Mani, Srinivasan; Murthy, G.V.S.
Abstract: Background: There are different estimates of disability prevalence reported in India due to the differences in definitions and methodologies. Reliable data is needed to plan effective disability inclusive strategies. Objective: The objective of this study was to determine the prevalence and risk factors associated with disability among adults ≥18 years of age in Prakasam district of Andhra Pradesh using the Rapid Assessment of Disability (RAD) tool. Methods: The RAD survey was conducted in 50 villages (clusters) of Ongole division of Prakasam district. A two-stage cluster random sampling was used. Within each village 80 participants were surveyed. Compact segment sampling was used to determine the houses included. A person was reported as disabled based on their responses to the functioning section of the RAD tool. Results: A total of 4134 adults were included. The overall prevalence of disability was 10.4% (431 adults). The highest prevalence of functional impairment was related to mobility (4.7%) followed by vision (2.1%) and fine motor (1.8%). The prevalence of psychological distress was 2.3%. Disability was significantly more prevalent in the poor socio economic group (OR 2.8; 95% CI: 1.5; 5.0) and among unemployed (OR 3.6; 95% CI: 2.3, 5.5). The prevalence of disability was strongly associated with age where, participants aged 70 years and over were eleven times more likely to report disability than younger age groups. Conclusion: The high prevalence of disability in the region points to disability being of public health concern and as a health condition needing urgent attention and specific interventions.